THE DEVELOPMENT OF INDONESIAâS TIDAL MODEL HYDROMOD VERSION 1.1 - Ihsan
There has been an increase in need of hydrodynamic information, one of it is tides. Tides are very useful resources that can be retracted from the ocean, and it can be used for many things in a variety of forms. There has been some global tidal models that can be an alternative to the costly and timetime consuming in situ observations. These global tidal models are not specified in Indonesia, so there has been an effort to create Indonesia’s Tidal Model which only covers Indonesia region. The previous Indonesia’s tidal model, called Hydromod version 1.0, was created with a bunch of flaws, one of it is bathymetry. It is the purpose of this presented paper to provide Indonesia’s tidal model with a better version, called Hydromod version 1.1, that is the development of the previous version. The study domain covers a whole of Indonesia region. The methods of producing the tidal model is by hydrodynamic modelling, using a modelling software, called Delft3D. The tidal model of three scenarios; west monsoon, east monsoon, and one year, are produced. The validation are using a one year data of 15 tidal referenced stations of Badan Informasi Geospasial (BIG). It is found that the average root mean square error of the data is 0.453 m in west monsoon and 0.413 m in east monsoon, with the highest value in Java Sea and Makassar Straits, and version 1.1 is better than version 1.0 with the comparison of 10 stations over 5 stations.